Parabolic Dish Collector as a New Approach for Biochar Production: An Evaluation Study - Eman H. El-Gamal; Mohamed Emran; Osama Elsamni; Mohamed Rashad; Ossama Mokhiamar (Applied Sciences, 2022)
The main factors influencing biochar properties are feedstock biomass and pyrolysis operational conditions. A solar parabolic dish collector was proposed as a new green approach to the pyrolysis process. The technique of this reactor was designed to produce biochar from sesame feedstock (SF) by concentrating solar radiation. This research aims to compare the main physical and chemical properties of biochar produced by the solar reactor to those of the conventional reactor (muffle furnace, SB-3). Biochar produced by the parabolic dish collector was a heterogeneous brown color. Depending on color intensity, biochar was divided into the biochar formed around the inner sidewalls of the internal chamber (SB-1) and the biochar formed in the upper part of the internal chamber (SB-2). Generally, the physiochemical properties of the SB-2 biochar were similar to the SB-3 biochar, while SB-1 biochar was similar to SF. This was because the temperature distribution was not uniform in the solar reactor. The proposed solar parabolic dish collector needs some modifications to upgrade the biochar production to be close to that produced by the electric instrument. SB-2 is preferred as a soil amendment depending on its pH, cation exchange capacity (CEC), elemental composition, ion molar ratio (H/C, O/C, and (O+N)/C), and acidic functional groups.